Alternate realities : how science shapes our vision of the world - Davis, Joel, 1948- (New York : Plenum, 1997)
Examines the ways in which thinkers throughout history have used their imaginations to lead them to scientific discoveries, and discusses how those advances and new theories shape the ways in which people perceive their world.
Includes bibliographical references (p. 293-301) and index.
Choice.
Publisher's Weekly.
Science Books & Films (A.A.A.S.).
Adult
Keywords: Reality; Science -- Philosophy; Vision; Reality; Science -- Philosophy; Vision